Cognitive and neurobehavioral benefits of an enriched environment on young adult mice after chronic ethanol consumption during adolescence - Rico Barrio, Irantzu; Peñasco, Sara; Puente, Nagore; Ramos, Almudena; Fontaine, Christine J.; Reguero, Leire; Giordano, Maria Elvira; Buceta, Ianire; Terradillos, Itziar; Lekunberri, Leire; Mendizabal Zubiaga, Juan; Rodríguez de Fonseca, Fernando; et al. (My University, 2018)
Binge drinking (BD) is a common pattern of ethanol (EtOH) consumption by adolescents. The brain effects of the acute EtOH exposure are well-studied; however, the long-lasting cognitive and neurobehavioral consequences of BD during adolescence are only beginning to be elucidated. Environmental enrichment (EE) has long been known for its benefits on the brain and may serve as a potential supportive therapy following EtOH exposure. In this study, we hypothesized that EE may have potential benefits on the cognitive deficits associated with BD EtOH consumption. Four-week-old C57BL/6J male mice were exposed to EtOH following an intermittent 4-day drinking-in-the-dark procedure for 4 weeks. Then they were exposed to EE during EtOH withdrawal for 2 weeks followed by a behavioral battery of tests including novel object recognition, novel location, object-in-place, rotarod, beam walking balance, tail suspension, light¿dark box and open field that were run during early adulthood. Young adult mice exposed to EE significantly recovered recogni tion, spatial and associative memory as well as motor coordination skills and balance that were significantly impaired after adolescent EtOH drinking with respect to controls. No significant permanent anxiety or depressive-like behaviors were observed. Taken together, an EE exerts positive effects on the long-term negative cognitive deficits as a result of EtOH consumption during adolescence. Keywords alcohol, behavior, binge drinking, cognition, environmental enrichment, therapy